(untitled) (Journal of Economic Research & Business Administration, 2016)
The research of this work is aimed at analyzing and building effective systems project risk management, in order to enhance the effectiveness of the risk management process. The article discusses the most relevant as- pects of risk management at the enterprises of the Republic of Kazakhstan, which occur in practice. One of the main issues are the groups of project risks, which include the risks that do not require active management and risks management that requires constant use of different techniques or require active man- agement. The article also discussed the methods of risk management in the cur- rent economic conditions, which are divided into resultfocused (active) and inertial (passive).